Malignant Acanthosis Nigricans Sine Malignancy - Jeevankumar B; Thappa Devinder Mohan; Karthikeyan Kaliaperumal (Wolters Kluwer Medknow Publications, 2003)
Malignant acanthosis nigricans is associated with extensive lesions and mucosal involvement. It may precede, occur simultaneously with or develop following the clinical onset of malignancy. We herewith describe a 28 year old woman with progressive generalized malignant acanthosis nigricans without any detectable malignancy or endocrinopathy.